A comparison of sensory attribute profiles and liking between regular and sodium-reduced food products. (September 2019) - Nguyen, Ha; Wismer, Wendy V.
Abstract: Few studies have compared consumer sensory product attribute profiles and their influence on liking of regular and sodium-reduced foods. This study compared sensory profiles and overall liking between regular and sodium-reduced foods and examined the influence of consumption frequency of dietary sodium sources (DSS) on consumer sensory perception. One hundred adult consumers (70 women) assessed four pairs of commercially available regular and sodium-reduced products (potato chips, pickles, cooked ham, chicken noodle soup) that contribute substantial sodium to the Canadian diet. Products were assessed for overall liking (9-point hedonic scale), saltiness (5-point Just-About-Right scale) and defining sensory attributes (3-point Rate-All-That-Apply scale). Consumers indicated their consumption frequency of 13 groups of DSS on a DSS Food Frequency Questionnaire (DSS-FFQ). Sodium-reduced foods were perceived with reduced saltiness and intensity differences of other sensory attributes. Saltiness was a key driver of pickle liking; sodium-reduced pickles were liked more than regular pickles. However, decreased intensity in saltiness and several sensory attributes of sodium-reduced chips (oily, flavorful) and ham (seasoning, juicy) did not change liking. Decreased intensity in all evaluated attributes decreased liking of sodium-reduced soup. Penalty analysis revealed opposing sub groups within the study population whose liking decreased or increased with reduced product saltiness, confirming the challenge to please the taste preferences of every consumer. Hierarchical cluster analysis of DSS-FFQ data stratified participants into low ( n  = 27), moderate ( n  = 33) and high ( n  = 40) consumption frequency of DSS. Consumption frequency of DSS influenced sensory perception inconsistently across products and unique liking drivers were identified for each consumer segment. This knowledge can aid development of sodium-reduced foods for targeted consumer segments. Graphical abstract: Unlabelled Image Highlights: Sensory profiles differed for each regular and sodium-reduced food product. Liking of regular and sodium-reduced products were different for pickles and soup. Sub groups within the study population responded differently to sodium reduction. Consumption level of dietary sodium sources affected consumer sensory perception. Unique liking drivers were identified for each consumer segment.